2021
DOI: 10.3389/fpls.2021.700925
|View full text |Cite
|
Sign up to set email alerts
|

Plant and Fungal Genome Editing to Enhance Plant Disease Resistance Using the CRISPR/Cas9 System

Abstract: Crop production has been substantially reduced by devastating fungal and oomycete pathogens, and these pathogens continue to threaten global food security. Although chemical and cultural controls have been used for crop protection, these involve continuous costs and time and fungicide resistance among plant pathogens has been increasingly reported. The most efficient way to protect crops from plant pathogens is cultivation of disease-resistant cultivars. However, traditional breeding approaches are laborious a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…So far CRISPR has shown some impressive results in achieving precise genetic modification at single or multiple gene targets. , The CRISPR-Cas9 system has been used to improve and incorporate several desirable traits in plants, of which betterment in disease resistance is one such trait. Besides their application in plants, CRISPR systems have also been used to target proteins that are known to play key roles in the interaction between fungal and oomycete pathogens and host plants . This has helped in better understanding of the underlying molecular mechanisms of host–pathogen recognition and ultimately developing screening systems for disease resistance.…”
Section: Recent Developments In Nucleic Acid Based Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far CRISPR has shown some impressive results in achieving precise genetic modification at single or multiple gene targets. , The CRISPR-Cas9 system has been used to improve and incorporate several desirable traits in plants, of which betterment in disease resistance is one such trait. Besides their application in plants, CRISPR systems have also been used to target proteins that are known to play key roles in the interaction between fungal and oomycete pathogens and host plants . This has helped in better understanding of the underlying molecular mechanisms of host–pathogen recognition and ultimately developing screening systems for disease resistance.…”
Section: Recent Developments In Nucleic Acid Based Detectionmentioning
confidence: 99%
“…Besides their application in plants, CRISPR systems have also been used to target proteins that are known to play key roles in the interaction between fungal and oomycete pathogens and host plants. 47 50 There exist multiple strategies for determining disease resistance in plants through the CRISPR-Cas system: (i) by introducing desired mutations within the coding regions via HDR, (ii) by alterations, deletions, modifications, or inclusion of the cis element in the promoter region, (iii) by knocking-out susceptible factor-encoding genes, (iv) by knocking-out negative regulators involved in defense responses in plants (e.g., TcNPR3), (v) by altering the amino acid sequence of the receptor proteins pertaining to surfaces for evading pathogen effectors (e.g., AtBAK1), and/or (vi) by refinement in key regulators associated with the defense response in plants (e.g., BnWRKY70). 51 Common approaches to execute CRISPR-Cas mediated plant genome editing are via the following ways: (i) transformation of sgRNA along with the Cas nuclease into the plant genome of interest, usually mediated by Agrobacteriummediated transformation (AMT), (ii) DNA-free editing using polyethylene glycol (PEG)-mediated transformation of protoplast by delivering a cargo of ribonucleoprotein (RNP) complex which essentially carries the Cas protein and desired sgRNA into the plant host cell, (iii) RNP complex delivered directly into plant embryo cells through means of biolistic delivery.…”
Section: Aptamer Based Approach For Plant Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its simplicity and specificity, CRISPR-Cas9 technology has been applied to different aspects of fungal research. For instance, CRISPR/Cas9 system has been utilized to study fungal pathogenicity ( 15 ), to facilitate genetic engineering for secondary metabolite production ( 12 ) such as increased gibberellic acid production in Fusarium fujikuroi ( 11 ) and boost pneumocandin B0 productivity in Glarea lozoyensis ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complete sequencing of the grapevine genome ( Jaillon et al, 2007 ) has identified novel genes, analyzed structural gene variants, discovered new single nucleotide polymorphisms, and clarified regulatory regions. These insights enable precision breeding using GenEd tools ( Capriotti et al, 2020 ; Paul et al, 2021 ). The clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) system is currently one of the most powerful GenEd techniques available.…”
Section: Introductionmentioning
confidence: 99%